2018
DOI: 10.1111/dom.13312
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal dose of atrasentan by evaluating the exposure‐response relationships of albuminuria and bodyweight

Abstract: This study aimed to identify the optimal dose of the endothelin‐1 receptor antagonist atrasentan with maximal albuminuria reduction and minimal signs of sodium retention, as manifested by increase in bodyweight. Data from the RADAR‐JAPAN studies were used, evaluating the effect of 0.75 or 1.25 mg/d of atrasentan in 161 patients with type 2 diabetes and kidney disease. Individual pharmacokinetic parameters were estimated using a population pharmacokinetic approach. Subsequently, changes in the urinary albumin‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…In this study, dose-response analysis indicated that 0.75 mg/ day atrasentan exerted a similarly significant benefit on albuminuria with less incidence of fluid retention vs a dose of ≥1.25 mg/day, suggesting that 0.75 mg/d atrasentan is optimal to provide renal protection with fewer safety concerns. This result is consistent with a previous post hoc analysis of the RADAR-JAPAN study, 36 which evaluated the exposureresponse relationships of albuminuria and body weight, and suggested that 0.75 mg/day atrasentan is the optimal dose for kidney protection with maximal efficacy and minimal fluid retention risks. Even so, it is still not possible to state that atrasentan does not increase the risk of CHF.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, dose-response analysis indicated that 0.75 mg/ day atrasentan exerted a similarly significant benefit on albuminuria with less incidence of fluid retention vs a dose of ≥1.25 mg/day, suggesting that 0.75 mg/d atrasentan is optimal to provide renal protection with fewer safety concerns. This result is consistent with a previous post hoc analysis of the RADAR-JAPAN study, 36 which evaluated the exposureresponse relationships of albuminuria and body weight, and suggested that 0.75 mg/day atrasentan is the optimal dose for kidney protection with maximal efficacy and minimal fluid retention risks. Even so, it is still not possible to state that atrasentan does not increase the risk of CHF.…”
Section: Discussionsupporting
confidence: 91%
“…This high variability in response to atrasentan has been observed before in phase 2 studies 3,6 . In an earlier, comparatively small phase 2 trial, a greater albuminuria reduction was observed in Asian patients compared with North American patients, which was linked to higher atrasentan plasma concentrations in Asian patients 9,10 . In the current study, the albuminuria response was similar between Asian and Caucasian patients.…”
Section: Discussionsupporting
confidence: 81%
“…The relationship between plasma exposure and albuminuria indicates that additional albuminuria lowering can be achieved by increasing the plasma exposure using a higher dose of atrasentan. However, the maximum dose is limited by the fluid‐retention effects of atrasentan, and increasing the atrasentan plasma exposure will also result in more fluid retention 10 . This highlights the need for establishing a therapeutic window, during which fluid retention is kept at a minimum, while albuminuria lowering is optimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This range in plasma exposure corresponded to a balance between kidney protection and fluid retention, which favored kidney protection, and was therefore used as reference. 7 Association between plasma exposure and long-term outcomes Parametric time-to-event models were developed to investigate the association between atrasentan plasma exposure and both composite outcomes. For both outcomes, model development initiated by evaluation of several model structures that could adequately describe the hazard of developing an event over time in the placebo group.…”
Section: Estimation Of Plasma Exposurementioning
confidence: 99%